“I had something to say, and I’m saying it now”: Rhetorical and linguistic construction of the media genre of the personal account - Halyna Kryzhanivska; Tatyana Yakhontova; Yulia Godis; Lyubomyr Borakovskyy (Ibérica)
The personal account is an endemic genre of women’s magazines. In this first-person story, a woman shares her experience on a problem of potential interest for the magazine’s audience and offers a solution to the problem. Although the personal account has already become an object of critical sociological analysis, psychological inquiry, and media studies, it remains underinvestigated from a linguistic perspective. This paper offers insights into the rhetorical organization and language of personal accounts by applying genre, narrative and sentence triad analyses to the study of its instances published in the Cosmopolitan. It shows that rhetorical and linguistic construction of this media genre ensures the imposing of the magazine’s ideology upon its readers and helps to build their global community. The findings of the study can be used in media literacy courses to develop university students’ critical thinking skills by helping them to understand how global ideology of women’s magazines is coded in the media genre of the personal account. The data collected in this study can also be utilized for training the journalistic skills of conveying personal experiences and writing inspirational media stories. Furthermore, they can contribute to raising female readers’ awareness of the function-form relationships within this genre and make them better prepared for either resistance or conscious acceptance of its ideological impact.